Technical training for shooting goals for one-side oriented players in the UEFA Women`s Euro 2009 - Bergier, J.; Niewolna, N. (Journal of Kinesiology and Exercise Sciences, 2012)
Aim of the study. In contemporary women`s football we can observe an increase in the importance of versatile preparation of players both in terms of motor activity and technique. What is essential in the play is the ability to take quick decisions i.e. to play one on one or cooperate with partners. It made us do research into: (1) determining the level of symmetry and asymmetry of shots at goal, (2) see through the topography of the shots Józef Bergier, Natalia Niewolna taking into consideration the spots of players taking shots and the goal`s sectors, (3) analyze the foot symmetry when taking penalties, (4) determining the successful shot technique, (5) pointing at the percentage of one-onone and teamwork actions which were successful. Material and methods. The material was an analysis of 84 goals during 25 matches of the UEFA Women`s EURO 2009 in Finland. Results. Amongst the analyzed goals only 33.9% were scored with the left foot, while 66.1% were scored with the right foot. The observation of symmetry taking into consideration the pitch zone and goal sectors showed higher symmetrization of actions. From the right pith zone 55.4% of goals wee scored while from the left one 44.6%. Whereas the right sector of the goal was aimed at 44.6% of cases and the left one - in 55.4%. Among 49 players scoring goals for their team only 5 showed the ability of scoring goals with both right and left foot. An important question the goals analysis is the technique of shots. More goals were scored with foot (81.2%) than with head (18.8%). In the foot shots the inside of the foot was used (35.7%) and inner-foot volley (22.9%). Conclusion. It was found that the shots at goal featured significant asymmetry. Among the successful actions teamwork is very important.